2019
DOI: 10.1007/s11419-019-00466-1
|View full text |Cite
|
Sign up to set email alerts
|

New-generation azaindole-adamantyl-derived synthetic cannabinoids

Abstract: Purpose This work reports the synthesis and pharmacological and analytical data for a new series of recently identified azaindole-adamantyl-derived synthetic cannabinoids (SCs). Methods Each SC was synthesised using an efficient and divergent synthesis, and assessed by electron ionisation mass spectrometry (EIMS). The cannabimimetic activity of each compound was conducted using a fluorometric imaging plate reader (FLIPR) assay. Results The described EIMS method and retention time by gas chromatography were abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…As part of the synthesis of 3‐carboxylate ( 28 ) and 3‐carboxamide ( 29 ) azaindoles (Scheme ), Longworth et al have suggested that the presence of an electron withdrawing pyridyl N‐atom in the azaindole core may hinder acylation at the C‐3 position of the azaindole ring. However, functionalization of the azaindole C‐3 position of 30 – 33 has been demonstrated to proceed smoothly, when treated with trifluoroacetic anhydride in the presence of aluminum chloride, to give SCRA intermediates 34 – 37 in moderate to excellent yields (63–95%) (Scheme ) …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…As part of the synthesis of 3‐carboxylate ( 28 ) and 3‐carboxamide ( 29 ) azaindoles (Scheme ), Longworth et al have suggested that the presence of an electron withdrawing pyridyl N‐atom in the azaindole core may hinder acylation at the C‐3 position of the azaindole ring. However, functionalization of the azaindole C‐3 position of 30 – 33 has been demonstrated to proceed smoothly, when treated with trifluoroacetic anhydride in the presence of aluminum chloride, to give SCRA intermediates 34 – 37 in moderate to excellent yields (63–95%) (Scheme ) …”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of 3‐carboxylate ( 28 ) and carboxamide ( 29 ) azaindole SCRAs via C‐3 acylation of 1‐ N ‐pentyl azaindoles 30–33, in the presence of AlCl 3 and trifluoroacetic anhydride, to give intermediates 34 – 37 . Basic hydrolysis of 34 – 37 affords the corresponding carboxylic acid analog series represented by 38 which can then be converted to the desired ester ( 28 ) or amide ( 29 ) series . R = n ‐pentyl…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations